Surgical Treatment of a Trimalleolar Ankle Fracture Diagnosed Six Weeks after the Injury - Yaniel Truffin Rodriguez; Rafael Esmandy Gámez Arregoitía; Osmany Pérez Martínez (Medisur)
Early diagnosis of traumatic injuries significantly changes patient outcomes. This statement remains true for the ankle since delay in treatment of ankle injuries can hinder its proper function. For these reasons, the case of a 29-year-old patient of rural origin treated at the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos is presented. The patient stated that he had suffered a horse fall six weeks earlier and presented with functional disability in addition to pain in his right ankle. A supra-syndesmotic fibular fracture, a medial malleolar fracture and a posterior malleolar fracture were diagnosed. To repair this injury, the Gatellier-Chastang approach was used for reduction and adequate fixation of the posterior malleolus. Osteosynthesis of the supra-syndesmotic fracture with a plate and screws was subsequently performed. Finally, the medial malleolar fracture was fixed with a malleolar screw. Six months after the surgery, the ankle showed normal ranges of dorsiflexion and plantar flexion; the edema was not significant and there was no pain when walking or resting.